2024
DOI: 10.1161/jaha.123.032965
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer‐Measured Behavior Patterns in Incident Cerebrovascular Disease: Insights for Preventative Monitoring From the UK Biobank

Stephanie J. Zawada,
Ali Ganjizadeh,
Gian Marco Conte
et al.

Abstract: Background The goal was to compare patterns of physical activity (PA) behaviors (sedentary behavior [SB], light PA, moderate‐to‐vigorous PA [MVPA], and sleep) measured via accelerometers for 7 days between patients with incident cerebrovascular disease (CeVD) (n=2141) and controls (n=73 938). Methods and Results In multivariate models, cases spent 3.7% less time in MVPA (incidence rate ratio [IRR], 0.963 [95% CI, 0.929–0.998]) and 1.0% more time in SB (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Since then, sensor-based technologies, such as accelerometers, have been applied to investigate the predictive potential of behavioral monitoring outside of clinical settings [ 15 ]. Using one week of accelerometer monitoring, a large population cohort study of adults in the UK Biobank found that accelerometer sensors may capture significant aberrations in hourly movement patterns linked with depression, such as changes in sleep and sedentary behavior, before a CeVD diagnosis [ 16 ]. In the Rotterdam Study longitudinal population cohort, significant deviations in basic and instrumental activities of daily living (BADL and IADL) and mood, as captured by the Mini-Mental State Examination (MMSE), may emerge within the 7 years leading to a stroke [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, sensor-based technologies, such as accelerometers, have been applied to investigate the predictive potential of behavioral monitoring outside of clinical settings [ 15 ]. Using one week of accelerometer monitoring, a large population cohort study of adults in the UK Biobank found that accelerometer sensors may capture significant aberrations in hourly movement patterns linked with depression, such as changes in sleep and sedentary behavior, before a CeVD diagnosis [ 16 ]. In the Rotterdam Study longitudinal population cohort, significant deviations in basic and instrumental activities of daily living (BADL and IADL) and mood, as captured by the Mini-Mental State Examination (MMSE), may emerge within the 7 years leading to a stroke [ 17 ].…”
Section: Introductionmentioning
confidence: 99%